2021
DOI: 10.1016/j.diabet.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and outcome in patients with COVID-19: A dose–response meta-analysis

Abstract: Highlights Obesity was associated with mortality and severity in patients with COVID-19. Dose–response meta-analysis demonstrate an increase of 5% risk for poor outcome for every 5 kg/mg 2 increase in body mass index. The relationship departed from linearity and became steeper from 30–35 kg/mg 2 onwards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
161
1
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(175 citation statements)
references
References 38 publications
6
161
1
7
Order By: Relevance
“…Analysis for heterogeneity was limited due to the fact that only two studies reported comorbidities that are associated with increased mortality in COVID-19 patients. These comorbidities are obesity (OR 1.55), hypertension (OR 2.21), diabetes (Risk Ratio [RR] 2.38), cardiovascular diseases (RR 2.25), and chronic obstructive pulmonary disease (OR 4.36) ( Huang et al., 2020 ; Pranata et al., 2020b , c ; Pranata, Lim, Huang, Raharjo & Lukito, 2020a ; Pranata, Huang, Lim, Wahjoepramono & July, 2020d ). Ideally, exploration of heterogeneity can be performed using meta-regression, however, it cannot be performed due to the lack of studies.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis for heterogeneity was limited due to the fact that only two studies reported comorbidities that are associated with increased mortality in COVID-19 patients. These comorbidities are obesity (OR 1.55), hypertension (OR 2.21), diabetes (Risk Ratio [RR] 2.38), cardiovascular diseases (RR 2.25), and chronic obstructive pulmonary disease (OR 4.36) ( Huang et al., 2020 ; Pranata et al., 2020b , c ; Pranata, Lim, Huang, Raharjo & Lukito, 2020a ; Pranata, Huang, Lim, Wahjoepramono & July, 2020d ). Ideally, exploration of heterogeneity can be performed using meta-regression, however, it cannot be performed due to the lack of studies.…”
Section: Discussionmentioning
confidence: 99%
“…22 Nevertheless, there are several factors that commonly coexists in patients with hip fracture, namely advanced age, obesity, and various comorbidities which are associated with increased severity and mortality of COVID-19. 8e11, 14,15,29,30 Because of reduced functional reserves and weakened immune function, these individuals are more adversely affected by SARS-COV-2 infection. The poor prognosis can be attributed to a combination of these factors rather than purely attributed to a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation in patients with coronavirus Disease-2019 (COVID-19) ranges from mild to critical, with multiple complications requiring ventilator support [ 1 , 2 ]. Patients with comorbidities are at higher risk of developing a more severe condition [ [3] , [4] , [5] , [6] , [7] ]. Simple and non-invasive assessments are helpful to identify patients at higher risk for severe outcome that requires more intensive monitoring and respiratory support.…”
Section: Introductionmentioning
confidence: 99%